Impact of spectral filtering in coexistence of noise-like pulse and dissipative soliton - Jiajing Lang; Chenyue Lv; Baole Lu; Jintao Bai (APL Photonics)
With the introduction of the Lyot–Sagnac filter, the laser enables the coexistence of noise-like pulse (NLP) and dissipative soliton (DS) outputs with switchable wavelength intervals, which is observed for the first time. A simulation model of a ytterbium-doped mode-locked fiber laser is also constructed, and the filtering effect is found to play an important role in the generation of NLP and the coexistence of NLP and DS in the mode-locked fiber laser based on a semiconductor saturable absorber mirror through numerical simulation. The study contributes to a deeper investigation of the NLP generation mechanism and provides new possibilities for switchable pulse types and wavelength light sources.